A Case Study of a Culinary Tourism Campaign in Germany: Implications for Strategy Making and Successful Implementation. (February 2013) - Ottenbacher, Michael C.; Harrington, Robert J.
Tourism organizations are recognizing the potential of culinary tourism as a powerful tool to promote destinations. Despite this recognition, the knowledge about how to successfully develop and implement a culinary tourism strategy is limited. The objective of this case study is to explore the key issues in the strategic process of a culinary tourism campaign based on a recently introduced initiative in South Germany. Specifically, this study assesses implications drawn from this campaign using a multiple lens from strategic management applied to culinary tourism initiatives. Six key areas emerged that were associated with culinary tourism success: (a) the strategy itself, (b) cooperation among stakeholders, (c) leadership issues, (d) culinary profile promotion, (e) communication of quality, and (f) enhancing tourist perceptions. The implications of this study highlight some of the differences in "what is" and "what should be" for regional initiatives.